Извлечение липидов из отработанного фильтрующего порошка методом контактной экстракции - Омельченко, Юлия Евгеньевна; Демидов, Игорь Николаевич (НТУ "ХПИ", 2016)
В статье представлены результаты исследования извлечения липидов из отработанного фильтрующего порошка (зажиренный перлит) методом контактной экстракции. Установлены рациональные параметры процесса экстракции с использованием в качестве растворителей гексана и сивушного масла. Показано, что использование данных растворителей позволяет снизить остаточную масличность фильтрующего порошка ниже 2 % и максимально извлечь воскоподобные вещества.

The article presents the results of a study of lipid extract from the spent filter powder contact extraction method. Rational parameters of the extraction process using hexane as the solvent and fusel‒oil. It is shown that the use of these solvents can reduce the residual oil content filtering powder below 2%, that provides with the opportunity to recommend it to be recycled at the oil winterization stage. Moreover, this contact extraction method allowed recovery of more than 98% of waxen substances from the used filter powder. This perlite regeneration approach provides with the opportunities to return the adsorbent to the stage of waxen substances filtration, utilize neutral lipids for technical and feeding purposes, and recover a valuable product - waxen substances used in different fields of national economy.
The using percolation extraction for recovery of lipids from the secondary products of oil industry
Keywords: воскоподобные вещества; сивушное масло; гексан; растительный воск; contact extraction; hexane